Revisiting rates of return to agricultural R&D investment - Nin-Pratt, Alejandro; Magalhaes, Eduardo (International Food Policy Research Institute, 2018)
This study proposes the use of partial least squares to determine the key parameters of the perpetual inventory method model of capital stock as a new approach to calculate research and development (R&D) knowledge stocks and R&D elasticities. This approach avoids most of the major problems encountered in the literature that lead to obtaining very high and implausible rates of return to agricultural R&D...Using this approach, we obtain an average R&D elasticity for low- and middle-income (LM) countries of 0.23 and an average rate of return to R&D investment of 6.0 percent, bigger than the average discount rate of 4.2 percent for these countries. Results show that 60 percent of LM countries in our sample are underinvesting in agricultural R&D, as they can get higher returns by investing in this activity than in activities that return the social discount rate.